2x-(-4)=2

Simple and best practice solution for 2x-(-4)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(-4)=2 equation:


Simplifying
2x + -1(-4) = 2

Multiply -1 * -4
2x + 4 = 2

Reorder the terms:
4 + 2x = 2

Solving
4 + 2x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 2x = 2 + -4

Combine like terms: 4 + -4 = 0
0 + 2x = 2 + -4
2x = 2 + -4

Combine like terms: 2 + -4 = -2
2x = -2

Divide each side by '2'.
x = -1

Simplifying
x = -1

See similar equations:

| -8x^4+72x^5/12x^5 | | 27r+55=190 | | p=2(2)+2(89) | | 1000x^2+600x=x-1 | | 4x-7x-14=-3x+3-14 | | p+p+49+p+49=144 | | p+p+49+(p+49)=144 | | x+5+3x-1=7.6 | | 3(4k+14)=10k-2k(k-7) | | 6x=-p/3-2p | | 0.18(y-1)+0.20y=0.02y-0.09(40) | | 2*x-1=15 | | 9-(3n-4)=7-4n | | 53=25+250m | | ((2x^4)/7)-((9x^2)/14) | | 156+65h=351 | | 9m+14m+10=-5 | | 7.20h=57.60 | | 4(x-7)+2(2x+6)=7(x-3)+7 | | -5.1-(-1.4)=x | | 2x+2+-3=5x+8 | | 4+11=x+2 | | I=8A/(T+B) | | -7n+11=5n-17 | | l+2l+(l+7)=115 | | .60b=.72 | | -8b-6(b-7)=-2b-2(2b+7) | | 1/2*5.4(7+5) | | I=8A/T+B | | 0.49/0.04=x | | x^2+(x+3)*(x+3)=89 | | 3y-8x=21 |

Equations solver categories